Treatment of Keloids Using Plasma Skin Regeneration Combined with Radiation Therapy Under the Evaluation of Patient and Observer Scar Assessment Scale - Ting W; Chong Y; Xu J; Huang J; Yu N; Liu Z (Dove Medical Press, 2021)
Wenyun Ting,1,* Yuming Chong,1,2,* Jing Xu,2 Jiuzuo Huang,1 Nanze Yu,1 Zhifei Liu1 1Department of Plastic and Aesthetic Surgery, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People's Republic of China; 2Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhifei LiuDepartment of Plastic and Aesthetic Surgery, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People's Republic of ChinaEmail liuzfpumch@163.comPurpose: Keloids are caused by uncontrolled excessive proliferation of fibrous tissue. Multiple treatment strategies including steroid injection, surgical excision, laser therapy and radiation therapy have been reported. Few studies have evaluated the performance of plasma skin regeneration (PSR) in the treatment of keloid. This study aimed to evaluate the effectiveness of PSR combined with radiation therapy for keloids on different body parts.Patients and Methods: A total of 71 patients with 98 keloids were enrolled in this study. Keloids < 4 mm thick underwent single-dose PSR, while keloids ≥ 4 mm thick were administered compound betamethasone injection beforehand. Radiation therapy was administered after 24 hours and again 7 days later after PSR. The outcome was evaluated using the patient and observer scar assessment scale at 12 months post-treatment.Results: Patient-reported average scores for all keloids significantly decreased from 35.05± 9.94 to 21.84± 7.04 (p < 0.05). Keloids on face and neck, chest, and back responded better than those on shoulders and limbs. The recurrence rate was observed to be 15.3% (15 out of 98). Adverse effects were mild.Conclusion: PSR combined with radiation therapy is an effective and safe strategy to treat keloids. Location could be a factor that affects curative effects.Keywords: keloid, plasma skin regeneration, radiation therapy, POSAS, recurrence rate